3D Mapping of Bone Channel of Blood Supply to Femoral Head in Proximal Femur - Wu, Shenghui; Quan, Kun; Wang, Wei; Zhang, Yingqi; Mei, Jiong (Frontiers in Surgery, 2022)
Background: A detailed depiction of nutrient foramina is useful for defining guidelines and minimising iatrogenic damage during hip surgery. Therefore, this study aimed to define the location and frequency of nutrient foramina in the proximal femur using mapping techniques. Methods: One hundred dry human cadaveric proximal femurs, comprising 56 left and 44 right femurs, were scanned using a three-dimensional scanner, with scanning distance 200 mm, precision 0.01 mm, and measuring point 0.04 mm. The image resolution of 1,310,000 pixels was obtained. Digital imaging models were acquired from the proximal femur surface. All the nutrient foramina in each model were identified and marked. The nutrient foramina models were superimposed on one another and oriented to fit a standard template of the femur’s proximal aspect. Three-dimensional mapping in the proximal femur’s nutrient foramina was performed. Results: The nutrient foramina’s location and dense zones were identified. The dense zones were distributed along the vascular course and gaps between the muscle attachment sites. Eighteen dense zones were identified and found to be location-dependent. They were located in the central part of the fovea capitis femoris, subcapital and basicervical areas of the femoral neck, and muscle attachment gaps of the femoral trochanter. Conclusions: The terminal branch of the nutrient vessels entering the nutrient foramina is at risk for iatrogenic damage during hip surgeries, especially in cases of close bone exposures. There are 18 dense zones that need to be considered for a safer approach to the proximal femur. To minimise iatrogenic damage to the nutrient vessels entering the nutrient foramina, the dense areas should be avoided when technically possible.